Parabrahman symbolism and the majesty of Prambanan Temple: Analyze its role in global Hindu traditions - Ashutosh Pareek; Ni Nyoman Sri Widiasih; Tina Manandhar (Dharmakirti : International Journal of Religion, Mind and Science, 2026)
Background: Prambanan Temple, one of the largest Hindu temple complexes in Southeast Asia, can be understood not only as an architectural monument but as a theological system that materializes the concept of Parabrahman, the absolute, infinite principle underlying all existence. This study aims to analyze how architectural structure, spatial organization, and visual narratives within the temple articulate the relationship between transcendental unity and divine manifestations in Hindu theology. Methods: This research employs a qualitative interpretive approach integrating library research, field observation, visual-architectural documentation, and semi-structured interviews with selected experts. Data were analyzed through thematic analysis, interpretative phenomenological analysis (IPA), and visual-semiotic analysis, supported by methodological triangulation to ensure analytical rigor. Findings: The findings reveal that the tripartite structure dedicated to the Trimurti (Brahma, Vishnu, and Śiva) represents a hierarchical cosmology in which Parabrahman is not directly depicted but symbolically mediated through spatial stratification, sacred geometry, and narrative reliefs. The central dominance of the Śiva temple reflects a theological synthesis in which multiplicity converges into a unified metaphysical principle. Furthermore, the reliefs function as visual exegesis, translating abstract cosmological doctrines into accessible symbolic forms that guide spiritual understanding and ritual practice. Conclusion: This study concludes that Prambanan Temple operates as a form of material theology, bridging metaphysical concepts and lived religious experience, and reinforcing the continuity of Hindu theological discourse beyond its Indian origins. Its significance lies in its capacity to encode complex philosophical ideas into enduring architectural and visual forms. Novelty/Originality of this article: The novelty of this research lies in its integrative analytical framework that combines theological hermeneutics, iconographic analysis, and integral consciousness theory to position Prambanan Temple as an active epistemic medium for constructing and transmitting the concept of Parabrahman, an approach that remains underexplored in existing scholarship.